APLIKASI CHEMDRAW DAN AVOGADRO UNTUK MENINGKATKAN PEMAHAMAN DAN MINAT DALAM BIDANG KIMIA - Emmy Yuanita; Sudirman Sudirman; Maria Ulfa; Ni Komang Tri Dharmayani; Iwan Sumarlan; I Made Sudarma (Jurnal Pendidikan dan Pengabdian Masyarakat, 2018)
In the industrial era 4.0, it is expected that the technology-based education system can be realized specifically in chemistry. One alternative in improving understanding and interest in chemistry is by ChemDraw and Avogadro applications. This research was conducted by providing training to teachers and students of ChemDraw and Avogadro applications which before and after the field data was collected by questionnaire. Significant data shown by chemistry teachers in Lombok island are few who know ChemDraw and hardly know about Avogadro. The hardest part of learning chemistry is to imagine the structure and bond in the molecule. From this exercise programmed participants are able to draw molecules both 2D and 3D. In the end the participants can draw simple to supramolecular structures with ChemDraw and Avogadro applications. Hopefully this activity can function to increase students' interest in learning chemistry.